Assessing Groundwater Quality, and Non-Carcinogenic Health Risks from Fluoride and Nitrate Contamination: A Case Study in the Kherlen River Basin, Mongolia - Enkhjargal, Togtokhbayar; Uchral, Enkhbaatar; Odsuren, Batdelger; Byambasuren, Zorigt; Chinzorig, Sukhbaatar; Munkhtur, Batsukh (Mongolian Journal of Geography and Geoecology, 2023)
In arid and semi-arid regions, where groundwater serves as the main source of drinking and domestic water for the population. Continuous consumption of water that does not meet drinking water standards can have a negative effects on human well-being. The purpose of this study is to investigate the quality and composition of groundwater in the Kherlen river basin, as well as to estimate the risk of non-cancerous diseases caused by fluoride and nitrate pollution to human health. Fieldwork was conducted in June 2023, and a total of 37 samples were collected and analyzed from the deep and shallow groundwater in the study area. Water quality (major ions) was analyzed according to approved standard methods and procedures. The assessment of non-carcinogenic health risks rising from nitrate and fuoride in different age groups (infants, children, and adults) using the methodology outlined by the United States Environmental Production Agency (USEPA). The findings revealed that 73% (27 out of 37 samples) failed to meet the requirements outlined in the drinking water standard MNS 0900:2018 and the World Health Organization (WHO) recommendations for various parameters, including pH, electrical conductivity (EC), total dissolved solids (TDS), fluoride, nitrate, total hardness, calcium, and magnesium. Specifically, 43.2% of all samples exhibited fluoride concentrations higher (ranging from 1.57 to 7.9 mg/l) than the MNS 0900:2018 and WHO-recommended levels (0.7-1.5 mg/l). Moreover, 21.6% fell below the specified limits, registering fluoride concentrations ranging from 0.29 to 0.67 mg/l. The nitrate concentration in the studied wells ranged from 1.0 to 582.3 mg/l, with 24.3% of all samples exceeding the MNS 2018 standard (50 mg/l) and only 2.7% surpassing the WHO-recommended limit of 45 mg/l. Human health risk indices (HI) were calculated for different age groups. The resulting HIs ranged from 0.182 to 12.985 for adult males, 0.224 to 22.209 for females, and 0.261 to 28.582 for children. Notably, 78.34% of children, 67.57% of adult women, and 64.86% of men exhibited HI values greater than 1, indicating a potential risk to human health posed by fluoride and nitrate-induced non-carcinogenic diseases. Газрын доорх усны чанар, фтор болон нитратын хүний эрүүл мэндэд учирч болзошгүй эрсдэлийн судалгаа: Хэрлэн голын сав газрын жишээн дээр ХУРААНГУЙ: Хуурай, хагас хуурай бүс нутагт газрын доорх ус нь хүн амын унд, ахуйн усны гол эх үүсвэр болдог. Чанарын шаардлага хангаагүй усыг тогтмол хэрэглэх нь хүний эрүүл мэндэд сөргөөр нөлөөлдөг. Энэхүү судалгааны зорилго нь Хэрлэн голын татамд орших газрын доорх усны чанар, найрлагыг судлахаас гадна фтор, нитратын бохирдлоос үүдэлтэй хүний эрүүл мэндэд учруулж болзошгүй хавдрын бус өвчлөл үүсгэх эрсдэлийг тооцоход оршино. Тус судалгааны хээрийн ажлыг 2023 оны 6-р сард хийж гүйцэтгэсэн бөгөөд судалгааны талбайд орших гүний болон бага гүний газрын доорх уснаас нийт 37 сорьц цуглуулан шинжлэн дүгнэлээ. Усны чанарыг (үндсэн ионууд) батлагдсан стандарт арга, аргачлалын дагуу шинжилсэн ба фтор, нитратын хавдрын буc өвчлөл үүсгэх эрсдэлийн хор аюулын үзүүлэлт (HQ) болон хор аюулын индексийг (HI) АНУ-ын байгаль орчныг хамгаалах агентлаг (USEFA 2018)-ийн стандарт аргын дагуу янз бүрийн насны бүлгүүдэд тооцлоо. Судалгааны дүнгээр нийт 37 сорьцоос 27 нь буюу 73% нь рН, EC, TDS, фтор, нитрат, нийт хатуулаг, кальци, магни зэрэг үзүүлэлтүүдээр ундны усны стандарт MNS 0900:2018 болон ДЭМБ (2017)-ийн зөвлөмж стандартын шаардлага хангахгүй байна. Фторын агууламжаар нийт сорьцын 43.2% нь MNS 0900:2018 болон ДЭМБ (0.7-1.5)-ын зөвшөөрөгдөх хэмжээнээс их (F 1.57-7.9 мг/л), 21.6% нь бага (F 0.29-0.67 мг/л) байна. Ундны усан дахь нитратын агууламжийг MNS 2018 стандартад 50 мг/л, ДЭМБ-ийн зөвлөмжид 45 мг/л гэж заасан байдаг бөгөөд судалгаанд хамрагдсан худгуудад нитрат (NО3-)-ын агууламж 1.0-582.3 мг/л илэрсэн. Энэ нь нийт сорьцын 24.3% нь MNS 2018 стандарт, 2.7% нь ДЭМБ-ийн зөвлөмжид заасан хязгаараас хэтэрсэн байна. Хор аюулын чанарын индекс (HI)-ийн тооцоогоор HI нь насанд хүрсэн эрэгтэйд 0.182-12.985, эмэгтэйд 0.224-22.209, хүүхдэд 0.261-28.582-ын хооронд байна. Фтор, нитратаас шалтгаалсан хавдрын бус өвчлөл үүсгэх HI-ийн утга нь насны бүлгүүдэд ялгаатай байна. HI нь хүүхдэд 78.34%, насанд хүрсэн эмэгтэйчүүдэд 67.57%, эрэгтэйчүүдэд 64.86% нь (HI>1)-ээс дээш их байгаа нь хүний эрүүл мэндэд эрсдэл учруулах магадлал өндөр байна. Түлхүүр үгс: Газрын доорх усны хэрэглээ, фтор, нитрат, эрүүл мэндийн эрсдэл